Multidrug Resistant Tuberculosis (MDR-TB) Factors: Literature Review - Subairi, Moh; Muhith, Abdul; Zahro, Chilyatiz (Chakra Brahmanda Lentera Institute, 2023)
Background: Multidrug-resistant tuberculosis (MDRTB) is the biggest problem in preventing and eradicating TB in the world. MDR-TB occurs if the tuberculosis germs are resistant to various first-line OAT, at least two drugs, namely isoniazid and rifampicin. The emergence of MDR-TB cases presents new obstacles and challenges to the effectiveness of TB control programs due to difficult diagnosis, high rates of therapy failure, and death. This literature review aims to determine the factors that cause multidrug-resistant tuberculosis (MDR-TB). Methods: The method used in this article is a literature review using journal databases from Pubmed and Google Scholar in the 2020-2023 time period with the keywords